2021
DOI: 10.1093/clinchem/hvab058
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Immature Reticulocytes in Dried Blood Spots by Mass Spectrometry

Abstract: Background Immature reticulocytes (IRC) are the first cells to respond to changes in erythropoiesis. For antidoping applications, measurement of IRC may improve detection of blood doping practices. Unfortunately, this small cell population has limited stability in liquid blood samples and is difficult to measure with optimal precision. We developed a method to measure 3 IRC membrane proteins in dried blood spots (DBS) to monitor changes in erythropoiesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 37 publications
0
14
2
Order By: Relevance
“…The average longitudinal precision of CD71/B3, FECH/B3, RET% and IRF%, across 9 subjects was 15 ± 3%, 24 ± 6%, 10 ± 2%, and 19 ± 4%, respectively. The longitudinal precision for RET% and IRF% observed in this study are lower than previously reported 15,27 …”
Section: Resultscontrasting
confidence: 91%
See 2 more Smart Citations
“…The average longitudinal precision of CD71/B3, FECH/B3, RET% and IRF%, across 9 subjects was 15 ± 3%, 24 ± 6%, 10 ± 2%, and 19 ± 4%, respectively. The longitudinal precision for RET% and IRF% observed in this study are lower than previously reported 15,27 …”
Section: Resultscontrasting
confidence: 91%
“…Twenty microliters of K2EDTA venous blood was spotted onto DBS cards and stored at room temperature in a desiccator cabinet. DBS spots were excised from the card and extracted in a 96‐well plate as previously described 15 . Briefly, DBS spots were washed in a series of buffers for 1.5 h to remove the soluble proteins.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due, at least in part, to ease of collection in pediatric populations, simplicity of transport, and robust testing methods for multiple analytes. While other studies have used DBS cards for research, few have transitioned to translational or clinical applications [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] . To this end, serological testing from DBS cards has the potential to be useful early in an epidemic or pandemic to better understand both symptomatic and asymptomatic spread of disease in difficult to reach populations particularly those far from testing centers, or in undeveloped countries.…”
Section: Discussionmentioning
confidence: 99%
“…DBS sampling is currently performed clinically for newborn screening [11] , [12] . DBS sampling has also been proposed for monitoring changes in erythropoiesis and other biologically relevant molecules in the fight against doping in professional sports [13] , [14] , [15] , drug screening [16] , and for the diagnoses of infectious diseases including hepatitis C virus [17] , [18] , cytomegalovirus [19] and HIV [20] . The varied utility of DBS sampling is further reflected by the stability and retrieval of analytes like microRNA [21] , protein [22] and sphingolipids [23] for sensitive molecular assays and mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%